A New Anatomically Based Nomenclature for the Roots and Root Canals-Part 2: Mandibular Molars - Denzil Valerian Albuquerque; Jojo Kottoor; Natanasabapathy Velmurugan (Hindawi Limited, 2012)
Several terminologies have been employed in the dental literature to describe the roots and root canal systems of mandibular molars with no consensus being arrived at, thus far. The anatomical relation of roots and their root canals were identified and a naming system was formulated. The proposed nomenclature attempts to make certain essential modifications to the traditional approach to accommodate the naming of various aberrations presented in mandibular molars. A simple, yet extensive nomenclature system has been proposed that appropriately names the internal and external morphology of mandibular molars.